2021
DOI: 10.1089/whr.2020.0107
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and the Female Nurse: A Narrative Review of the Current State of Research and Future Directions

Abstract: Background: The female nurse exhibits a multitude of personal and environmental characteristics that renders this population especially prone to fatigue. The consequences of fatigue in nurses are widespread and impactful at the personal, organizational, and societal levels. These include high injury rates and burnout in the nurse and poor patient and organizational outcomes. Objective: This article discusses the implications of fatigue in female nurses, including the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…Some previous studies have also revealed that age could contribute to the development of fatigue in nurses [ 48 , 49 ]. The current findings regarding the association between gender and fatigue were similar to those of the Thompson study [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…Some previous studies have also revealed that age could contribute to the development of fatigue in nurses [ 48 , 49 ]. The current findings regarding the association between gender and fatigue were similar to those of the Thompson study [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…Self-rated fatigue slightly decreased in the intervention and control groups, but the between-group difference was not statistically significant in this study. Fatigue in nurses is widely prevalent and consequential because nurses are inevitably exposed to various personal and environmental characteristics leading to fatigue, such as long working hours and successive night shifts [ 34 , 35 , 36 ]. According to previous studies, regular exercise could help mitigate fatigue and help restore physical/emotional function more rapidly by augmenting recovery [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue in nurses is widely prevalent and consequential because nurses are inevitably exposed to various personal and environmental characteristics leading to fatigue, such as long working hours and successive night shifts [ 34 , 35 , 36 ]. According to previous studies, regular exercise could help mitigate fatigue and help restore physical/emotional function more rapidly by augmenting recovery [ 34 , 35 , 36 ]. For example, nurses engaging in regular exercise reported lower fatigue levels and better recovery outcomes compared to those who did not regularly exercise [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that night shifts are associated with increased fatigue ( 17 , 36 , 37 ). Mild fatigue may be imperceptible, but accumulative fatigue can have serious consequences, even death from overwork ( 38 ).…”
Section: Discussionmentioning
confidence: 99%